Análise da eficiência de membranas poliméricas Comerciais para regeneração óssea em defeitos cranianos de ratos. - Araújo, Lana Karine (2022)
Bone regeneration challenges the medical and dental fields, being limited in extensive defects, which motivates the search for barrier membranes, biocompatible and resorbable devices designed to inhibit soft tissue invagination and favor osteogenesis. The consumer market has osteopromotive membranes validated for clinical use, but the comparison of the performance of these therapeutic options is little known. The objective of this work was to analyze the efficiency of different commercial polymeric membranes applied to guided bone regeneration using the experimental model of critical size defect in rats. An 8mm bone defect was created in the calvaria of each of the 60 adult male Wistar rats in this study. Animals received one of the following six treatments: LuminaCoatTM bovine collagen membrane (G1), SurgitimeTM PTFE membrane (G2), GenDermTM bovine cortical bone membrane (G3), PratixTM PLGA membrane (G4), TechgraftTM bovine pericardium membrane (G5) or blood clot (C-). The animals were euthanized at 1 or 3 months after surgery, for histological and histomorphometric analysis of the percentage presence of newly formed bone, connective tissue and biomaterial. For each parameter, ANOVA with Tukey's post-test was applied in the analysis of the means between groups and control at each experimental time and the paired Student's t test was used in the analysis of the means of the same group between the two different experimental times, considering p <0.05. There was a variable amount of newly formed bone adjacent to the edges of the bone defects, superior to the islets of bone in its most central region, with a progressive increase in centripetal osteogenesis between 1 and 3 months for all groups and C-. The connective tissue was more abundant in the C- front of the groups, evolving from a loose extracellular matrix in 1 month to a more fibrous model in 3 months. It was possible to observe the presence of material in up to 3 months in all groups except for C-, with no noticeable degradation for G2 and G4, while G1 and G3 showed evident degradation of the material between 1 and 3 months. New bone means at 1 month were higher for G2 compared to G1, G4 and G3 as well as for G5 and C- compared to G3, at 3 months there were no differences between the groups and between 1 and 3 months for G4, which had greater bone gain. Means of connective tissue at 1 month were higher for C- against G3, G5, G2 and G1, at 3 months for G4 and G5 against G1 and G2 as well as for C- against G2 and between 1 and 3 months for C-, which had a significant decrease in connective tissue. The biomaterial means at 1 month were higher for G1 compared to G4, in 3 months for G2 compared to G4 and G3 as well as for G5 compared to G3 and between 1 and 3 months for G1, G3 and G5, which had a significant decrease in biomaterial. Considering the results achieved over the 3 months of the experiment and the individual requirements for choosing an ideal regenerative membrane, the decreasing order of efficiency in terms of osteopromotive capacity would be: G2 > G4 > G5 > G1 > G3. As for the lower tendency to connective tissue formation, the decreasing order of efficiency would be: G2 > G1 > G5 > G3 > G4. Finally, regarding the presence of biodegradation, from the most accelerated modality to the non-resorption modality, the decreasing order of efficiency would be: G3 > G4 > G1 > G5 > G2. The difficulty in meeting the set of specificities for choosing an ideal regenerative membrane raises further discussions about the intrinsic factors of each biomaterial, such as composition, origin and thickness, differential modulators of its performance in guided bone regeneration.